2017
DOI: 10.1177/1087054716685837
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Symptoms and Disorders in College Students With ADHD

Abstract: College students with ADHD are more likely to have a lifetime history of an anxiety disorder and are at greater risk for some anxiety symptoms and associated features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…For instance, researchers found that up to 25% of children with ADHD have comorbid anxiety disorders ( Wolraich et al, 2005 ). O’Rourke et al (2020) believe that people with ADHD are at a greater risk of having anxiety symptoms and its associated features than people without ADHD. Similarly, Gau et al (2010) noticed that children and adolescents with persistent ADHD have a higher risk of developing anxiety disorders than those without persistent ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, researchers found that up to 25% of children with ADHD have comorbid anxiety disorders ( Wolraich et al, 2005 ). O’Rourke et al (2020) believe that people with ADHD are at a greater risk of having anxiety symptoms and its associated features than people without ADHD. Similarly, Gau et al (2010) noticed that children and adolescents with persistent ADHD have a higher risk of developing anxiety disorders than those without persistent ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to increase the number of specialized psychiatric services in which clinicians with specific training and expertise in the assessment and treatment of ADHD enable faster diagnosis and implement effective treatment. phobia than panic disorder [8]. Substance use disorder (SUD) is twice as common in individuals with ADHD compared to the general population, particularly in the use of alcohol, nicotine, cannabis, and cocaine [9].…”
Section: Resultsmentioning
confidence: 99%
“…Panic disorder has been associated with cyclothymic and dysthymic temperamental traits in major depressive patients presenting with atypical features [ 49 ] and with short hypomanic episodes in patients with recurrent brief depressions [ 50 ]. In contrast, only a few studies have assessed panic comorbidity in adults with ADHD, and conflicting findings have emerged from comparisons with healthy controls [ 51 , 52 ]. In addition, panic disorder has been demonstrated as the least prevalent anxiety disorder in children with ADHD [ 53 ], and polygenic risk for ADHD has been negatively associated with panic disorder in a Japanese study [ 54 ].…”
Section: Discussionmentioning
confidence: 99%